Strengthening Debt Management Practices : Lessons from Country Experiences and Issues Going Forward. (Policy Papers; Policy Paper, 2007)
This paper reviews Bank-Fund staff experience with strengthening public debt management (PDM) frameworks and capacity in developing countries. In 2001, the IMF and the World Bank developed sound practice guidelines in this area, followed by a pilot program to assist 12 countries develop and implement reforms. In addition, an assessment of PDM has been incorporated into surveillance work, where relevant, and included in other Bank and Fund advisory and technical assistance work. Based on these, the paper draws key lessons, identifies the continuing challenges facing debt managers, and proposes further capacity building and advisory work in PDM. The 12 countries in the pilot program were Bulgaria, Colombia, Costa Rica, Croatia, Indonesia, Kenya, Lebanon, Nicaragua, Pakistan, Sri Lanka, Tunisia, and Zambia.